Viral Justice: The Influence of Social Media Culture on the Independence of Law Enforcement - Flora, Henny Saida; Taqyuddin Kadir (PT. Anagata Sembagi Education, 2026)
Social media culture has transformed the digital public sphere and significantly influenced law enforcement practices in Indonesia. The phenomenon of viral justice demonstrates how legal processes are increasingly exposed to public opinion pressure generated through online virality, functioning as a form of non-formal intervention beyond established legal mechanisms. This study aims to examine the impact of social media culture on the independence of law enforcement and its normative implications for the rule of law and due process of law. The research employs a normative juridical method using statutory, conceptual, and case approaches. The findings reveal that normative ambiguity within existing regulations has resulted in the absence of clear boundaries between digital freedom of expression and the protection of fair judicial processes. Consequently, law enforcement officials face reputational pressures that may shift decision-making from legal reasoning toward popularity-based responsiveness. This condition threatens judicial independence, undermines legal certainty, and creates unequal treatment between viral and non-viral cases. The study underscores the urgent need for explicit legal norms and strengthened institutional ethics to maintain a balance between digital freedoms and the integrity of the rule of law in the social media era.